Reciprocal crosses between Alabio and Mojosari ducks : early egg production - L.H Prasetyo; T Susanti (Indonesian Center for Animal Research and Development (ICARD), 2000)
alternative to increasing productivity and production efficiency. Crossbreeding has been used widely for increasing productivity, and in this experiment Alabio and Mojosari ducks were crossed reciprocally in order to evaluate their egg production and egg quality, when compared to their parental breeds. Four genotypes AA, AM, MA and MM were compared and each consisted of 50 layer ducks. Each animal was kept in individual cage, and individual egg production and egg quality were recorded. They were given layer feed containing 20% crude protein and 3000 kcal/kg metabolisable energy. Results showed that the crossbred ducks (AM and MA) laid eggs earlier than their parental breeds (AA and MM), and MA laid earlier than AM. The weight of first eggs of the crossbreeds did not differ significantly, AM was the same as MM and MA the same as AA. For the body weight at first lay, MA and AM weighed in between their parental breeds, AA was the heaviest and then followed by MA, AM and MM. For the 3-month egg production, MA ducks laid significantly more egg than the other 3 genotypes, and this is related to the age of first lay being the earliest. In terms of egg quality such as egg weight, yolk color, weight and thickness of shell, weight of the white and HU value, the crossbred ducks showed quality in between AA and MM. The AM ducks tended to be closer to MM and MA closer to AA, and this shows a strong influence of maternal effects. The average level of heterosis for weight of first egg is 2.41% and for 3-month egg production is 2.1%, but for MA cross the heterosis level is 11.69% for egg production. The overall results showed that crossbreeds between Alabio and Mojosari have the potential in improving production traits in the effort to increase productivity and production efficiency. Key words : Duck, crossbred, production egg